A Rare Case of Spontaneous Pneumocephalus Associated with Nontraumatic Cerebrospinal Fluid Leak - Murad Baba; Omer Tarar; Amer Syed (Case Reports in Neurological Medicine)
Introduction. Spontaneous nontraumatic pneumocephalus (PNC) and cerebrospinal fluid (CSF) leaks are both very uncommon conditions. We report a rare case of spontaneous pneumocephalus associated with CSF leak secondary to right sphenoid sinus bony defect without history of trauma. Case Description. 51-year-old Hispanic female with past medical history of hypertension and idiopathic intracranial hypertension (Pseudotumor Cerebri) presented to the emergency room complaining of headache and clear discharge from the right nostril. Physical examination was significant for right frontal sinus tenderness and clear discharge from right nostril. Computed Tomography (CT) scan of the brain showed moderate amount of extra-axial air within the right cerebral hemisphere indicative of pneumocephalus. CT scan of facial bones showed bony defect along the right sphenoid sinus with abnormal CSF collection. The patient was started on intravenous antibiotics for meningitis prophylaxis and subsequently underwent transsphenoidal repair of cerebrospinal fluid leak with abdominal fat graft. CSF rhinorrhea stopped completely after the surgery with near complete resolution of pneumocephalus before discharge. Conclusions. Early identification of pneumocephalus and surgical intervention can help decrease the morbidity and avoid possible complications. Idiopathic intracranial hypertension, although rare, can lead to CSF leak and pneumocepahlus.